The use of plant materials in culinary products out of yeasted dough - Arpul (Oleksiichuk), Oksana; Sylchuk, Tetiana; Zuiko (Kulinich), Vira; Tyshchenko (Usatiuk), Olena (My University, 2015)
The article deals with the technology of garlic donuts (pampushkas) enriched with schavnat (hybrid of spinach dock or patience dock and Tien Shan sorrel) as a source of plant protein. The influence of schavnat on the technological process and the quality of pampushkas was determined. The organoleptic properties and the physical and chemical properties such as titrated acidity, texture, specific volume, dough fermentation property and viscoplastic properties were investigated.We obtained a «Special pampushkas with garlic» with a high content in plant proteins which could be recommended for balancing the nutrient composition of population diet. У статті розглядається технологія пампушок, збагачених щавнатом (гібрид щавлю шпинатного чи шпинату англійського із щавлем тянь-шанським) як джерелом рослинного білка. Було визначено вплив щавнату на технологічний процес та якість пампушок. Було досліджено органолептичні та фізико-хімічні показники, такі як: титрована кислотность, текстура, питомий об’єм, бродильна активність і вязкопластичні властивості. Отримано «Спеціальні пампушками з часником» з високим вмістом рослинного білку, які можуть бути рекомендовані для збалансування структури харчування населення.
Keywords: schavnat; щавнат; schavnat powder; порошок щавнату; порошок щавната; yeasted dough; дріжджове тісто; дрожжевое тесто; garlic donut; пампушки; culinary products; кулінарні вироби; кулинарные изделия; кафедра готельно-ресторанної справи; кафедра технології ресторанної і аюрведичної продукції